DETERMINAN INDIVIDU TERHADAP PENGGUNAAN MOBILE BANKING: PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) (Studi pada Masyarakat Pengguna Mobile Banking di Kabupaten Lamongan) - Resita, Indri Nur Nur; Baridwan, Zaki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study purposes to examine the factors that influence individual intention to use mobile banking services by modified Technology Acceptance Model (TAM). The antecedent of individual intention to use mobile banking in this research are perceived usefulness, perceived ease of use, perceived risk, and attitude. This research was conducted at city of Lamongan residents who use mobile banking facility from Bank Mandiri, Bank BNI, and Bank BRI by survey method. A number of 200 questionnaires were distributed and 122 questionnaires have been received back can be used. The data were analyzed by Partial Least Square (PLS) using SmartPLS version 2.0M3 sofware. The result of study showed that perceived usefulness, perceived ease of use, and perceived risk affect individual attitude to use mobile banking. Attitude toward using affect an individual behavioral intention to use mobile banking. The implications of this research are relevant for bankng institutions and mobile banking analyst to consider the factors which influence an individual intention to use mobile banking in the development the information systems. Keywords: Technology Acceptance Model (TAM), mobile banking, perceived usefulness, perceived ease of use, perceived risk, attitude, behavioral intention.